Atomic-scale combination of germanium-zinc nanofibers for structural and electrochemical evolution - Gyujin Song (Nature Portfolio, 2019)
Alloy anode materials are receiving renewed interest. Here the authors show the design of Ge-Zn nanofibers for lithium ion batteries. Featured by a homogeneous composition at the atomic level and other favorable structural attributes, the materials allow for impressive electrochemical performance.